2016
DOI: 10.1002/aenm.201600516
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Water Oxidation Catalysis by Synergistic Interactions between Ni(OH)2 and Carbon Nanotubes

Abstract: capsulating the electrocatalysts. [27,[43][44][45][46] Recently, Zhao and coworkers [47] and Dai and co-workers [48,49] anchored Co, Ni-Fe based water splitting catalysts on multiwall carbon nanotubes (MWCNTs), these approaches not only enhanced the charge transportations but also increased the available catalytic sites. Although the obtained materials exhibit excellent activity toward water oxidation, the improvement are not significant compared to the original catalysts. Very recently, Zhao and co-workers [5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 59 publications
1
62
2
Order By: Relevance
“…Therefore, all subsequente lectrocatalytic tests were only focused on the optimal CP@Ni(OH) 2 electrode. After preactivation, the CP@Ni(OH) 2 electrode only needs overpotentials of 1.54 (h 10 = 308 mV) and 1.57 V( h 20 = 338 mV) to attain current densities of 10 and 20 mA cm À2 ,r espectively;t hese values compare favorably to those of otherN i-based OER catalysts recently reported in the literature, such as a-Ni(OH) 2 hollow spheres (h 10 = 331 mV), [34] b-Ni(OH) 2 nanoplates (h 10 = 444 mV), [34] b-Ni(OH) 2 nanoparticles (h 10 = 340 mV), [36] b-Ni(OH) 2 porousn ano-plates (h 10 = 360 mV), [29] NiFe 2 O 4 /a-Ni(OH) 2 compounds (h 10 = 340 mV), [43] Ni 2 Pn anowires (h 10 = 400 mV), [30] and electrodeposited Ni-P thin films (h 10 = 344 mV), [31] although they are not as good as those of b-Ni(OH) 2 /O-MWCNT hybrids (h 10 = 270 mV) [37] and Ni-P porousnanoplates (h 10 = 300 mV) [29] (Table S2). For comparison, the OER activities of bare CP andC P/RuO 2 electrodes were also measured.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, all subsequente lectrocatalytic tests were only focused on the optimal CP@Ni(OH) 2 electrode. After preactivation, the CP@Ni(OH) 2 electrode only needs overpotentials of 1.54 (h 10 = 308 mV) and 1.57 V( h 20 = 338 mV) to attain current densities of 10 and 20 mA cm À2 ,r espectively;t hese values compare favorably to those of otherN i-based OER catalysts recently reported in the literature, such as a-Ni(OH) 2 hollow spheres (h 10 = 331 mV), [34] b-Ni(OH) 2 nanoplates (h 10 = 444 mV), [34] b-Ni(OH) 2 nanoparticles (h 10 = 340 mV), [36] b-Ni(OH) 2 porousn ano-plates (h 10 = 360 mV), [29] NiFe 2 O 4 /a-Ni(OH) 2 compounds (h 10 = 340 mV), [43] Ni 2 Pn anowires (h 10 = 400 mV), [30] and electrodeposited Ni-P thin films (h 10 = 344 mV), [31] although they are not as good as those of b-Ni(OH) 2 /O-MWCNT hybrids (h 10 = 270 mV) [37] and Ni-P porousnanoplates (h 10 = 300 mV) [29] (Table S2). For comparison, the OER activities of bare CP andC P/RuO 2 electrodes were also measured.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, considerable research efforts have recently been de-voted to the search for efficient and inexpensive OER catalysts comprising earth-abundant elements, including transitionmetal oxides, [8][9][10] hydroxides, [11][12][13] perovskites, [14,15] phosphates, [16,17] sulfides, [18,19] and recently reported phosphides. [33][34][35][36][37][38][39][40] For example, Stern and Hu compared the OER performance of bulk Ni(OH) 2 films to that of Ni(OH) 2 nanoparticles and found that the Ni(OH) 2 nanoparticles only neededasmall overpotential (h)o f3 00 mV to deliver ac urrent density of 10 mA cm À2 (h 10 ), and thus, they substantially outperformed bulk Ni(OH) 2 films and demonstratedt he benefito fn anostructuring. Previous work on the OER performance of Ni(OH) 2 was primarily focusedo ne lectrodepositeda nd physically depositedt hin films.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, linear sweep voltammetry (LSV) was conducted to test the electrochemical behavior of the NiFe/Cu 2 O NWs/CF electrode in 1.0 m KOH, as shown in Figure 6a . [31] Cyclic voltammograms of the non-faradaic region were recorded at various scan rates, and the C dl and ECSA of the NiFe/Cu 2 ON Ws/CF electrode were calculated to be 98 mF cm À2 and 2450 cm 2 ,r espectively.S uch al arge ECSA is of great help for enhancing the catalytic activity for the OER. In contrast, the OER did not proceed with the Cu 2 ON Ws/CF electrode until the oxidation potentialw as increased to 1.55 V versusR HE (black line).…”
Section: Resultsmentioning
confidence: 99%